The ‘unforgettable’ experience of foreign language anxiety - Drakulić, Morana (Journal of Education Culture and Society, 2020)
Foreign language anxiety (FLA) has long been recognized as a factor that hinders the process of foreign language learning at all levels. Among numerous FLA sources identified in the literature, language classroom seems to be of particular interest and significance, especially in the formal language learning context, where the course and the teacher are often the only representatives of language. The main purpose of the study is to determine the presence and potential sources of foreign language anxiety among first year university students and to explore how high anxiety levels shape and affect students’ foreign language learning experience. In the study both the questionnaire and the interviews were used as the data collection methods. Thematic analysis of the interviews and descriptive statistics suggest that most anxiety-provoking situations stem from the language classroom itself.